The anti-UV properties of Saussurea involucrate Matsum. & Koidz. Via regulating PI3K/Akt pathway in B16F10 cells. (6th April 2021) - Gong, Guowei; Zheng, Yuzhong
Abstract: Ethnopharmacological relevance: Ultra Violet (UV) radiation is the major reason for reactive oxygen species (ROS) forming, skin cell damage, melanin production, and could horribly cause skin cancer. Saussureae Involucratae Herba (SIH) is the aerial part of Saussurea involucrata Matsum. & Koidz. This Material Medica is popular with both in Uyghur and Chinese medicines filed. SIH is one of the famous species of the Asteraceae family and which prescribed for skin protection from UV-induced damage according to China Pharmacopeia (2020). However, the detailed working mechanism involved is still not elucidated. Aim of the study: We would like to probe the potential transduction pathway of SIH against UV-induced skin cell damages in cultured B16F10 cells. Methods: Western blot, luciferase assay, laser confocal, RT-PCR and flow cytometer were employed here to verify the protective pharmaceutical value of SIH in cultured B16F10 cells after UV pre-treatment. Results: Our result revealed that SIH attenuates ROS formation after UV-induced damage in B16F10 cells in a dose-dependent manner. Moreover, the transcriptional and translational anti-oxidative encoding genes were up-regulated under the presence of SIH. Further studies showed that SIH activated transcriptional activity of anti-oxidant response element (ARE). Moreover, we found that SIH dramatically stimulates PI3K/Akt phosphorylation in cultured B16F10 cells, this result was further verified by its specific inhibitors, LY294002 and Tocris. Conclusion: Our findings concluded that SIH protect melanoma cells from UV damages via activating PI3K/Akt signaling and which could provide scientific evidence for anti-UV pharmaceutical values of this herbal extract. Graphical abstract: Image 1